(untitled) (Journal of the College of Basic Education, 2025)
This study addresses the problem of boundaries and classifications in Arabic grammar by examining five central concepts: conditionals, sentence, speech, exception, and the proper noun. The issue lies in the ambiguity of the demarcation between these concepts and the diversity of grammarians’ opinions, which has led to inconsistencies in classification and a lack of clarity in definitions.Among the key findings of the research is the proposal of new classifications for the sentence in Arabic based on its components, as well as the reinforcement of certain grammatical terms. This has contributed to a reconsideration of their meanings and highlighted their development over time.